(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores the transformative impact of digital payment systems on Small and Medium Enterprises (SMEs) in India. With the rapid adoption of digital technologies, SMEs have increasingly integrated digital payment solutions into their business operations. This study aims to assess the extent to which digital payment systems have influenced the growth, efficiency, and competitiveness of SMEs. By analyzing data collected from a diverse range of SMEs across various industries, the paper identifies key benefits, such as enhanced financial transparency, improved cash flow management, and increased customer satisfaction. Additionally, the study examines the challenges faced by SMEs in adopting digital payment methods, including technological barriers, cybersecurity concerns, and the need for regulatory support. The findings highlight the crucial role of digital payment systems in driving the digital transformation of SMEs and suggest policy recommendations to further facilitate this transition. This paper contributes to the understanding of how digital payments can be leveraged to enhance the economic contribution of SMEs in India.